2004
DOI: 10.1016/s0002-9440(10)63208-7
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Regulation of Inorganic Pyrophosphate and Osteopontin by Akp2, Enpp1, and Ank

Abstract: Tissue-nonspecific alkaline phosphatase (TNAP) hydrolyzes the mineralization inhibitor inorganic pyrophosphate (PP(i)). Deletion of the TNAP gene (Akp2) in mice results in hypophosphatasia characterized by elevated levels of PP(i) and poorly mineralized bones, which are rescued by deletion of nucleotide pyrophosphatase phosphodiesterase 1 (NPP1) that generates PP(i). Mice deficient in NPP1 (Enpp1(-/-)), or defective in the PP(i) channeling function of ANK (ank/ank), have decreased levels of extracellular PP(i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
493
3
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(533 citation statements)
references
References 40 publications
28
493
3
5
Order By: Relevance
“…Several human and mouse diseases with excessive or insufficient bone formation have been related to defects in, respectively, the phosphodiesterases (such as nucleotide pyrophosphatase/phosphodiesterase 1), which produce PPi (11,12), and the phosphatases (such as tissue-nonspecific alkaline phosphatase [TNAP]), which degrade PPi (13)(14)(15). The homozygous ank (progressive ankylosis) mouse has a loss-of-function nonsense mutation in the ank gene that codes for a regulator of PPi export, and these mice develop a condition characterized by pathologic calcium apatite crystal deposition in the synovial and subsynovial spaces, followed by chondro-osteophyte formation and eventual bony ankylosis of the affected joints (16).…”
Section: Conclusion Our Results Indicate That the Tnap Haplotype Rs3mentioning
confidence: 99%
“…Several human and mouse diseases with excessive or insufficient bone formation have been related to defects in, respectively, the phosphodiesterases (such as nucleotide pyrophosphatase/phosphodiesterase 1), which produce PPi (11,12), and the phosphatases (such as tissue-nonspecific alkaline phosphatase [TNAP]), which degrade PPi (13)(14)(15). The homozygous ank (progressive ankylosis) mouse has a loss-of-function nonsense mutation in the ank gene that codes for a regulator of PPi export, and these mice develop a condition characterized by pathologic calcium apatite crystal deposition in the synovial and subsynovial spaces, followed by chondro-osteophyte formation and eventual bony ankylosis of the affected joints (16).…”
Section: Conclusion Our Results Indicate That the Tnap Haplotype Rs3mentioning
confidence: 99%
“…However, since the intracellular pyrophosphate concentration is only in the micromolar range the relative contribution of ANK to extracellular pyrophosphate levels is likely to be smaller than the breakdown of ATP by NPPs [28]. At present, the biological role and function of ANK remains unclear.…”
Section: Generation and Regulation Of Extracellular Pyrophosphatementioning
confidence: 99%
“…Tissue non-specific alkaline phosphatase (TNAP) is the only alkaline phosphatase implicated in mineralisation and is the key enzyme involved in pyrophosphate breakdown [35,36]. Previous work has suggested that the opposing actions of NPP1 and TNAP may be critical in determining local extracellular phosphate and pyrophosphate levels [28,37]. Deletion or inactivation of one of these enzymes has a significant effect on the skeleton (see reviews [35,39]).…”
Section: Pyrophosphate As An Inhibitor Of Bone Mineralisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteopontin interacts with the αvβ3 integrin (Wozniak et al 2000) and mediates cell adhesion and differentiation, which in turn could alter cell phenotype and matrix mineralization. In osteoblasts, osteopontin production is coordinately regulated with elaboration of inorganic pyrophosphate, a potent inhibitor of hydroxyapatite crystal formation Harmey et al 2004). Thus, osteopontin may indirectly affect mineralization by altering levels of other crystal-regulating substances.…”
Section: Nih Public Accessmentioning
confidence: 99%